2019
DOI: 10.1055/s-0039-1693655
|View full text |Cite
|
Sign up to set email alerts
|

A Wide Comparison of Techniques for Repair of PAPVCs: One Institution's 20-Year Experience

Abstract: Background Different methods for surgical correction of partial anomalous pulmonary venous connection (PAPVC) exist. We evaluated the outcomes of four techniques regarding morbidity and mortality. Methods A total of 116 patients underwent PAPVC repair in our institution over a period of 20 years. Single-patch technique (n = 82 [71%], mean age: 18.59 ± 20.49 years), double-patch technique (n = 13 [11%], mean age: 43.18 ± 25.14 years), Warden's technique (n = 7 [6%], mean age: 10.04 ± 10.47 years), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…25 Buz et al 3 reported that extended incision across the cavoatrial junction during double-patch repair leads to significant higher rate of postoperative arrhythmias both at discharge and 1-year follow-up. Recently, Jaschinski et al 26 reported double-patch repair had statistically significant higher incidence of persistent arrhythmia (44%, p ¼ 0.035). In accordance with our result, although insignificant, the incidence of SND was higher in group B despite careful cavoatrial incision and adequate patch designing.…”
Section: Discussionmentioning
confidence: 97%
“…25 Buz et al 3 reported that extended incision across the cavoatrial junction during double-patch repair leads to significant higher rate of postoperative arrhythmias both at discharge and 1-year follow-up. Recently, Jaschinski et al 26 reported double-patch repair had statistically significant higher incidence of persistent arrhythmia (44%, p ¼ 0.035). In accordance with our result, although insignificant, the incidence of SND was higher in group B despite careful cavoatrial incision and adequate patch designing.…”
Section: Discussionmentioning
confidence: 97%
“…Stewart et al (13) showed a 55% incidence of supraventricular arrhythmias in the double-patch group, compared to significant lower incidence in singlepatch and Warden groups (24% and 0%, respectively). Similarly, a recent paper by Jaschinski et al (14) displayed analogous features, where patients treated with the double-patch technique had a significantly higher incidence of non-sinus rhythm.…”
Section: Discussionmentioning
confidence: 65%
“…Stewart et al 13 showed a 55% incidence of supraventricular arrhythmias in the double-patch group, compared to significant lower incidence in single-patch and Warden groups (24 and 0%, respectively). Similarly, a recent paper by Jaschinski et al 14 displayed analogous features, where patients treated with the double-patch technique had a significantly higher incidence of non-sinus rhythm.…”
Section: Discussionmentioning
confidence: 65%